2020
DOI: 10.3390/ijms21228480
|View full text |Cite
|
Sign up to set email alerts
|

Natural Health Products (NHP’s) and Natural Compounds as Therapeutic Agents for the Treatment of Cancer; Mechanisms of Anti-Cancer Activity of Natural Compounds and Overall Trends

Abstract: Most cancer therapeutics, such as tubulin-targeting chemotherapy drugs, cause cytotoxic, non-selective effects. These harmful side-effects drastically reduce the cancer patient’s quality of life. Recently, researchers have focused their efforts on studying natural health products (NHP’s) which have demonstrated the ability to selectively target cancer cells in cellular and animal models. However, the major hurdle of clinical validation remains. NHP’s warrant further clinical investigation as a therapeutic opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 154 publications
(225 reference statements)
0
12
0
Order By: Relevance
“…Moreover, it has been found that nontoxic concentrations of matrine sensitized multidrug-resistant K562 cells in two ways, namely, the reactivation of apoptosis and inhibition of drug efflux [ 142 ]. Matrine can downregulate the phosphorylation of NF-κB, restore pro-apoptotic factors, and inhibit anti-apoptotic factors, thus promoting endogenous apoptosis [ 143 ]. Matrine can also induce mitochondrial damage by promoting the proapoptotic genes Bax, Bid, Bad, and Bim, and downregulating the apoptosis-inhibiting genes Bcl-2, Mcl-1, and Bcl-XL to promote endogenous Apoptosis.…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
“…Moreover, it has been found that nontoxic concentrations of matrine sensitized multidrug-resistant K562 cells in two ways, namely, the reactivation of apoptosis and inhibition of drug efflux [ 142 ]. Matrine can downregulate the phosphorylation of NF-κB, restore pro-apoptotic factors, and inhibit anti-apoptotic factors, thus promoting endogenous apoptosis [ 143 ]. Matrine can also induce mitochondrial damage by promoting the proapoptotic genes Bax, Bid, Bad, and Bim, and downregulating the apoptosis-inhibiting genes Bcl-2, Mcl-1, and Bcl-XL to promote endogenous Apoptosis.…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
“…Beside the differences found in the diets described, the common denominator seems to be the high consumption of fruit and vegetables that is constantly present, and which guarantees a reduced onset of cancer [36,37]. To date, it is known that several natural bioactive compounds possess anticancer properties [38,39]. It is important to highlight that there are more than 100 natural plant-based compounds currently in clinical use as anticancer drugs [40].…”
Section: Natural Compounds and Cancermentioning
confidence: 99%
“…However, the drugs routinely used are rather toxic [ 21 ]. A good alternative is the application of natural anticancer compounds, like polyphenols [ 22 ]. Phenolic hydroxyl group-containing molecules indeed showed several anticancer effects, thanks to their antioxidant [ 23 , 24 ], anti-inflammatory [ 25 ], and anti-angiogenic properties [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%